Wartość życia ludzkiego w nauczaniu papieży Jana Pawła II, Benedykta XVI i Franciszka - Ozorowski, Mieczysław (Teologia i Moralność, 2018)
The article presents the teachings of Popes John Paul II, Benedict XVI and Francis on the value of human life. St. John Paul II has developed the foundations of the science of the value of life. All the last popes unequivocally teach that human life is sacred and possesses an inescapable dignity all the time from conception to its end in natural death. The value of human life is rooted in the creation of man in the image and likeness of God, and is independent of the quality of life and the way of human existence. All successors of St. Peter shows the life of a Christian in a supernatural perspective. They also remind us of the many dangers of life such as abortion, genetic manipulation, war, euthanasia. The great defender of human life was St. Pope John Paul II. Pope Benedict XVI and Pope Francis point to the social dimension of human life, emphasizing the need to improve the quality of human existence. It is so important that the modern world is lost by mixing the category of absolute value of human life with the unspecified quality of life category